The linkage of greenwashing perception and consumers' green purchase intention - Budi Setiawan; Anissa Yosephani (Business and Entrepreneurial Review, 2022)
This study analyzes the linkage between greenwashing perception and consumers' green purchase intention. There is a critical research gap regarding the strategic linkage between these two essential constructs in green marketing. The unit of analysis of this research is the individual, namely the consumer who knows about drinking water products in disposable gallon packaging. The sample size is 500 respondents, with the sampling technique is purposive sampling. Confirmatory factor analysis is used to test the validity and reliability of the instrument. The structural equation modelling (SEM) analysis was used to test the research hypothesis. The result shows that greenwashing perception has a negative and significant effect on consumers' green purchase intention. Greenwashing perception has a close relationship with consumers' green purchase intention. The lower the consumer's perception of greenwashing, the more their intention to buy environmentally friendly green products will increase.